2000
DOI: 10.1152/ajpgi.2000.279.6.g1148
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of the flavanone naringenin and its glycosides in rats

Abstract: Naringenin, the predominant flavanone in grapefruit, mainly occurs as glycosides such as naringenin-7- rhamnoglucoside or naringenin-7-glucoside. This study compared kinetics of absorption of naringenin and its glycosides in rats either after a single flavanone-containing meal or after adaptation to a diet for 14 days. Regardless of the diet, circulating metabolites were glucurono- and sulfoconjugated derivatives of naringenin. The kinetics of absorption of naringenin and naringenin-7-glucoside were similar, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
209
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(232 citation statements)
references
References 29 publications
19
209
0
4
Order By: Relevance
“…In the present study, hesperidin metabolites recovered in plasma were identified as glucuronides of hesperetin, among which a low part was also sulphated. To our knowledge, the nature of the metabolites of flavanones in human plasma has never been described in the literature, but our results are in agreement with the findings of animal studies (Peng et al, 1998;Choudhury et al, 1999;Felgines et al, 2000). Besides, the presence of glucuronides of flavanones has been reported in human urine (Fuhr & Kummert, 1995;Ameer et al, 1996;Lee & Reidenberg, 1998).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, hesperidin metabolites recovered in plasma were identified as glucuronides of hesperetin, among which a low part was also sulphated. To our knowledge, the nature of the metabolites of flavanones in human plasma has never been described in the literature, but our results are in agreement with the findings of animal studies (Peng et al, 1998;Choudhury et al, 1999;Felgines et al, 2000). Besides, the presence of glucuronides of flavanones has been reported in human urine (Fuhr & Kummert, 1995;Ameer et al, 1996;Lee & Reidenberg, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…In rats, rutinosides and neohesperidosides are not deglycosylated nor absorbed in the small intestine, but are converted into aglycones by the intestinal bacteria, and then absorbed in the caecum (Felgines et al, 2000;Griffiths & Barrow, 1972; Figure 3 Individual plasma concentration curves for hesperetin after ingestion of 1 l of orange juice. Concentration of aglycones were determined by HPLC with Coularray detection, after hydrolysis by a b-glucuronidase-sulphatase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification and measurement of flavonoid conjugates are key prerequisites to understand the role of these compounds, since these are the forms that will reach tissues and exert their biological effect. Previous studies of naringin (naringenin-7-O-rhamnoglucoside) metabolism have suggested that sugar moiety cleavage, by gut microflora a-rhamonosidases, is the first step of this pathway, leading to the formation of naringenin, which undergoes rapid glucuronidation or sulphatation in the intestine or liver (Fuhr & Kummert, 1995;Felgines et al 2000;Scalbert & Williamson, 2000). Most studies have applied enzymatic hydrolysis with sulphatase and glucuronidase in order to identify the aglycone naringenin, and thus the individual metabolic profiles are lost during the hydrolysis procedure (Fuhr & Kummert, 1995;Ishii et al 1996Ishii et al , 1997Hollman et al 1999;Erlund et al 2001;Bugianesi et al 2002;Manach et al 2003;Zhang & Brodbelt, 2004).…”
Section: Discussionmentioning
confidence: 99%